(untitled) (Research, Society and Development, 2021)
This article is the result of a research carried out at the Mestrado Profissional em Educação Profissional e Tecnológica (ProfEPT), in the Instituto Federal de Educação, Ciência e Tecnologia do Rio Grande do Norte, Campus Mossoró. Its objective is to reflect on the process of rapprochement between a community of artisanal fishermen and the teachers and technicians of the Curso Técnico Subsequente em Pesca do Instituto Federal de Educação, Ciência e Tecnologia do Ceará (IFCE), campus Acaraú. The project began as a field investigation in the district of Guriú, in Camocim-CE, where the community of artisanal fishermen is located. However, in the face of the Covid-19 pandemic and social isolation, the development of the investigation continued remotely with interviews and records of videos made by the fishermen themselves with the use of cell phones. The videos and photographic images produced a documentary that was presented to the professors and technicians of the Subsequente em Pesca del IFCE, campus Acaraú. The discussions and suggestions offered by the teachers in two rounds of conversations gave rise to a booklet with information about legislation, safety, associativism and the necessary care in the sale of fish.